The Philippines Parametric Catastrophe Risk Insurance Program Pilot : Lessons Learned - World Bank (World Bank, Washington, DC, 2021)
The Philippine Parametric Catastrophe Risk Insurance Program (the ‘parametric program’) represents a key milestone in this partnership. In July of 2017, the Philippines placed on the international financial markets a portfolio of catastrophe risk that transferred typhoon and earthquake risk from the Philippines through the World Bank to the international reinsurance market in local currency. In 2018, the GOP purchased a second insurance policy, doubling the amount of coverage. The two-year pilot has now ended, although many of the lessons learned and technical work undertaken have proved useful in the subsequent preparation and placement of the GOP catastrophe (CAT) bond in December 2019. As part of closing this activity, the World Bank commissioned a lessons-learned evaluation to help all par ties involved better understand the successes and challenges of the program, and guide their continued efforts to improve financial preparedness to disasters in the Philippines. The evaluation is also mean t to build the evidence base on parametric insurance and allow for knowledge sharing with similar programs that are being explored or implemented in other countries. This report discusses the findings from the evaluation.